IDENTIFIKASI FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN PAJAK DAERAH - Tahwin, Muhammad (Buletin Studi Ekonomi, 2014)
Abstract : Indentification of Factory that Affect local tax revenue. This study had a purpose to analyze local tax income in rembang regency according to factors, which affected the income for the period of 1992-2008. The data used in this study are primary and secondary data. This study applied a multiple regression analysis. the results obtained by the study. Show that per capita income, number of tourists and c group mining product had a positive and significant effect to the tax income. Number of industries and hotel room reservation did not have significant effect to the tax income of rembang regency. Variable of per capita income gives the dominant influence to the local tax income rembang regency.
Keywords: local tax income, Rembang Regency, number of tourist, c group mining